China’s Ecological Path - Nadić, Darko (Napredak, 2021)
For almost two decades, the People’s Republic of China has been on the path of complete environmental enlightenment and redesign of its character in the international community. China is becoming not only an active but also a dominant participant in the global fight against climate change. In addition, China is firmly determined to change its internal environmental situation and its policy of further industrial progress, harmonizing it with the generally accepted environmental goals of humanity. The paper presents the basic facts about certain historical and political causes of inadequate attitude towards the environment in China, as well as the radical ecological and political deviation from ignoring ecological problems to formulating ten new goals, ie ten ecological policies, which are contained in the new ideology of "ecological civilization". A special review in the paper is given to the ecological elements of the "Belt and Road" initiative and the previous Chinese achievements in ecological and technological development. The conclusion also suggests a direction for possible cooperation between China and Serbia in the field of that ecological-technological development.